Changes in the bacterial community composition of different habitats along a polluted river (Suquía River, Cordoba, Argentina) - Merlo, Carolina (2017)
The objective of the present study was to investigate the influence of environmental conditions on the bacterial community composition in water, sediment and riparian soil during different water flow periods. For this purpose, samples of three habitats (water, sediment and riparian soil) were collected from five polluted sites and one reference site along the Suquía River during high and low water flow periods. The pH, dissolved oxygen, conductivity and water temperature were measured ?in situ?, with total organic carboncontent, nitrate and ammonia concentration being evaluated for all samples. In addition, pH, conductivity and total N were determined in the sediment and riparian soil samples, and the bacterial community composition of water, sediments and riparian soil samples was monitored using restriction fragment length polymorphism of the 16S rRNA gene. The results showed that the bacterial community composition of water was different from that of sediments or riparian soil. A redundancy analysis indicated that the changes in the bacterialcommunity composition in the Suquía River were primarily correlated with variations in dissolved oxygen, conductivity and pH. The water bacterial community composition was very variable among sites and water flow periods, while that of sediments differed according to the water flow period, which was associated with temperature variation. Lastly, in riparian soil, differences were found in the bacterial community composition of the sites located before and after Cordoba city. Our findings suggest distinct distribution paerns in the bacterial community compositions of the three habitats evaluated